Mango Growing in the Florida Home Landscape - Jonathan H. Crane; Carlos F. Balerdi; Ian Maguire (EDIS)
Revised! HS2 (formerly FC-2), a 12-page fact sheet by Jonathan H. Crane, Carlos F. Balerdi, and Ian Maguire, provides homeowners with an expanded and reorganized basic reference for growing mango in the home landscape. Tables include information on characteristics of Florida mango varieties, cultural practices by month, fertilizer program, and nutritional values. Included in the Master Gardener Handbook. Published by the UF Horticultural Sciences Department, October 2005. Reviewed November, 2006.